PENERAPAN EVIDENCE BASE NURSING: PENERAPAN PEMAKAIAN ALAT PELINDUNG DIRI BAIK DAN BENAR DI RUANG HEMODIALISIS DALAM MENCEGAH HAI'S DI RSUD TARAKAN JAKARTA - Mahdina Maulani (2023)
Healthcare Associated Infections (HAI's) are infections acquired during treatment at health services. HAI's infections develop symptoms after 2 X 24 hours of hospitalization days where the patient has no symptoms of infection before being treated at a health service. One of the health workers who has a high vulnerability to infection transmission is a nurse. Compliance with the use of PPE is one of the control efforts for medical personnel and health workers so they are not exposed to infection. The aim of the study was to increase nurse compliance in using Personal Protective Equipment (PPE) and to determine the effect of SOP socialization on personal protective equipment (PPE) on the behavior of nurses in the hemodialysis unit in an effort to prevent the risk of infection. This study uses Wilcoxon statistical test analysis with a value (p-value <0.05). The results showed that there was a change between before and after the action was given (p-value 0.003). The conclusion of this study is that there is a significant change between the knowledge of nurses before and after the socialization of PPE SOP's. Suggestions for this research are strategies that can be carried out to increase knowledge by holding health education programs or health training